INFORMAL SECTOR AND INSTITUTIONS - ÖZER, Muhammed Yusuf (Theoretical and Practical Research in Economic Fields; Vol 13 No 2 (2022): TPREF, Volume XIII, Issue 2(26), Winter 2022, 2022)
In this paper, I investigate the relationship between informal sector size and various institutional quality variables: government stability, external conflict, internal conflict, corruption control, military influence over politics, religious tensions, ethnic tensions, law-and-order, democratic quality, and bureaucratic accountability. To this end, I use annual cross-country panel data covering 130 countries from 1990 to 2018. Having conducted a correlation analysis, the size of informal economy and institutional quality indicators are inversely linked. The most crucial institutional quality determinants are law-and-order (-0.53), bureaucratic quality (-0.51), military in politics (-0.45), corruption control (-0.42), and internal conflict (-0.35).